Paving Plant-Food-Derived Bioactives as Effective Therapeutic Agents in Autism Spectrum Disorder - Cruz-Martins, Natalia; Quispe, Cristina; Kirkin, Celale; Senol, Ezgi; Zulug, Asli; Ozcelik, Beraat; Cho, William C. (Hindawi Ltd, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder, where social and communication deficits and repetitive behaviors are present. Plant-derived bioactives have shown promising results in the treatment of autism. In this sense, this review is aimed at providing a careful view on the use of plant-derived bioactive molecules for the treatment of autism. Among the plethora of bioactives, curcumin, luteolin, and resveratrol have revealed excellent neuroprotective effects and can be effectively used in the treatment of neuropsychological disorders. However, the number of clinical trials is limited, and none of them have been approved for the treatment of autism or autism-related disorder. Further clinical studies are needed to effectively assess the real potential of such bioactive molecules.
Keywords: PLACEBO-CONTROLLED TRIAL; OPEN-LABEL TRIAL; RANDOMIZED CONTROLLED-TRIAL; VALPROATE-INDUCED AUTISM; ALTERNATIVE MEDICINE USE; YOUNG-CHILDREN; DOUBLE-BLIND; OXIDATIVE STRESS; GINKGO-BILOBA; VITAMIN-D